Sabedoria feminina na tradição discursiva dos folhetos de Leandro Gomes de Barros e José Costa Leite - Vieira, Fabianne Ramos de Souza (2018)
This research aims to study the Cordel literature Booklet from the issue of female wisdom in the poetics of two popular poets: Leandro Gomes de Barros e José Costa Leite. In the research, it was observed that the poets in question, in writing about women, expose the knowledge used by them, which places them in places of domination. Leandro Gomes de Barros and José Costa Leite, poets of Paraíba of different time and traditions, in their works they present, in common, the feminine theme, telling through the booklets about the woman in diverse faces and tricks. The theory of Discursive Traditions was chosen to support this study that involve factors integrated to the language and that are conditioned to a certain cultural, social and historical identity. Based on the discussions and the qualitative and multidisciplinary study, the research process was developed through the theoretical basis of: Cascudo (1953;1984), Santos (2006), Ortiz (1994), Koch (1997), Durand (1996), Duby (1991), Halbwachs (2006), Lee Goff (1996), Longhin (2014), Souza (1976), Sodré (1976), Zumthor (1993; 2005; 2010). These writings analyzed aim to investigate the movement of the voices of the poets in the tradition, from the individual and collective memory. From the collected material, a corpus was made up of four booklets of each poet: A sogra enganando o diabo, A alma de uma sogra, Como se amansa uma sogra, A história da Donzela Teodora, by Leandro Gomes de Barros (1865 – 1918) and A mulher do cabaré, Uma mulher carinhosa, A magia do beijo da mulher bonita, Beijo de mulher bonita e carinho de mulher feia, by José Costa Leite (1927). Through the studies of memory and Discursive Traditions it has been able to understand the social practices moving between the individual and collective traditions of the subjects throughout the ages, expressed in the chosen booklets. The analysis that develops indicates variations or movements of the texts, without, however, changing the founding structure, heritage of the medieval histories and the Portuguese colonizers; and observes how aspects of popular wisdom collaborate and involve the male imaginary about women.